2019
DOI: 10.1002/pbc.27717
|View full text |Cite
|
Sign up to set email alerts
|

Elevated tricuspid regurgitation velocity in congenital hemolytic anemias: Prevalence and laboratory correlates

Abstract: Elevated tricuspid valve regurgitation jet velocity (TRV ≥ 2.5 m/s) is associated with mortality among adults with sickle cell disease (SCD), but correlative biomarkers are not studied according to treatment exposure or genotypes. To investigate the associations between biomarkers and TRV elevation, we examined the relationship between TRV and hemolytic, inflammatory, and cardiac biomarkers, stratified by disease‐modifying treatments and SCD genotype. In total, 294 participants with SCD (mean age, 11.0 ± 3.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…The prevalence in our cohort is somewhere in-between these 2 reported values, given that the mean age of our study population was 12.0 ± 4.9 years. A recent study by Yates et al 25 reported a similar prevalence of elevated TR in their study group with a mean age of 11.0 ± 3.7 years. In our HU treatment group, there was a significant improvement in the number of patients with elevated TR from baseline to last visit (37% of patients with elevated TR at baseline, 11% of patients with elevated TR at last visit).…”
Section: Discussionsupporting
confidence: 64%
“…The prevalence in our cohort is somewhere in-between these 2 reported values, given that the mean age of our study population was 12.0 ± 4.9 years. A recent study by Yates et al 25 reported a similar prevalence of elevated TR in their study group with a mean age of 11.0 ± 3.7 years. In our HU treatment group, there was a significant improvement in the number of patients with elevated TR from baseline to last visit (37% of patients with elevated TR at baseline, 11% of patients with elevated TR at last visit).…”
Section: Discussionsupporting
confidence: 64%
“…Some studies have found that a higher TRV cut‐off of 3.0 m/second is more strongly associated with mortality than the 2.5 m/second cut‐off 38,39 . The definition of elevated TRV of ≥2.5 m/second has been adopted for studying children with SCD, 25‐29 although it is not clear that the same definition of elevated TRV would apply to both adults and children. The PUSH study enrolled a non‐SCD control group contemporaneous with the SCD patients, and we utilized this control group to define an elevated TRV to be ≥2.7 m/second, or more than 2 SD above the mean in non‐SCD controls.…”
Section: Discussionmentioning
confidence: 99%
“…30,[35][36][37] Some studies have found that a higher TRV cut-off of 3.0 m/second is more strongly associated with mortality than the 2.5 m/second cut-off. 38,39 The definition of elevated TRV of ≥2.5 m/second has been adopted for studying children with SCD, [25][26][27][28][29] although it is not clear that the same definition of elevated TRV would apply to both adults and children. [41][42][43] Serum ferritin also increases with inflammation or with hepatocellular damage in the absence of increased iron stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently showed that, in individuals with HbSS or HbSb 0 thalassemia not on disease-modifying therapies (DMTs), TRV elevation was strongly influenced by the degree of anemia. 22 Use of DMTs, such as hydroxyurea and chronic erythrocyte transfusions, have impacted the natural history of SCA by improving laboratory parameters of anemia and hemolysis, preventing acute complications, and preserving organ function. [23][24][25][26][27][28][29][30] However, data regarding their effect on TRV are conflicting.…”
Section: Introductionmentioning
confidence: 99%